Antimicrobial Properties and Microbiological Shelf-life of Aquilaria malaccensis Spray Dried Leaf Extract Powder - Hoo, Xiao Hui; Balkis A. Talip, (Enhanced Knowledge in Sciences and Technology, 2022)
Aquilaria is an evergreen woody tree which is well known for its resin-impregnated stem called agarwood. The leaves of Aquilaria are found to exhibit antioxidant, antidiabetic, anti-arthritic, antibacterial, antifungal, anti-inflammatory and hepatoprotective activities. Due to their potential as the raw ingredients and final products, Aqularia malaccensis leaves were extracted in ethanol and water for secondary metabolites that maintain their microbiological qualities during storage. Thus, this study aims to investigate the antimicrobial properties and shelf-life of the spray dried Aquilaria malaccensis leaf extract powder. Broth microdilution assay was used to determine the minimum inhibitory concentration (MIC) of the spray dried Aquilaria malaccensis leaf extract powder against the selected bacteria and fungi. The shelf-life analysis of the spray dried Aquilaria malaccensis leaf extract powder was analyzed by using standard plate count (SPC) method. It has been reported that there is no inhibitory effect of the spray dried Aquilaria malaccensis leaf extract powder against Escherichia coli, Staphylococcus aureus, Bacillus cereus, Aspergillus niger, Rhizopus oryzae and yeast. Water is more polar and effective in extracting the antimicrobial agents from the leaves of Aquilaria malaccensis than the ethanol. The shelf-life study of the spray dried Aquilaria malaccensis ethanol and aqueous leaf extract powder has shown that no microbial growth after 33 weeks or above. This can be explained by the application of spray drying that destroys the microorganisms and reduces the water activitiy of Aquilaria malaccensis leaf extract. In the future study, the shelf-life study of the spray dried Aquilaria malaccensis leaf extract powder can be carried out under accelerated condition.